Efektifitas Kebijakan Ruang Udara Terbuka terhadap Pembangunan Ekonomi Indonesia - Mende, Melisa Irianti; Amboro, Yudhi Priyo; H. Hutauruk, Rufinus (UNES Law Review, 2023)
The ASEAN Open Sky Agreement is one of the multilateral agreements, particularly among ASEAN countries, aimed at enhancing the economy through airspace. The ASEAN Open Sky Agreement is expected to be both a solution and a goal in developing the ASEAN economy, especially to enhance its competitiveness in the international world. This is to ensure that economic development among ASEAN member states can be achieved evenly. The concept of the ASEAN Open Sky Agreement presents significant opportunities, including substantial market access, substantial benefits, increased tourism attractiveness, and flight frequencies. The objective of this research is to analyze the impact and efforts of the Indonesian government in dealing with the implementation of the ASEAN Open Sky Agreement. It is further analyzed using the Legal Effectiveness Theory by Soerjono Soekanto and the Legal Development Theory by Prof. Mochtar Kusumaatmadja. The research methodology utilized is normative juridical. The research design employed in this study is descriptive analysis, and the data is obtained from secondary sources and analyzed qualitatively. From this study, it can be concluded that the impact includes the expansion of flight network coverage, the opening of flight options, and the establishment of broad distribution access through channels provided by partner airlines. Additionally, the agreements within the ASEAN Open Sky Agreement consist of three agreements that regulate air transport services, passenger and cargo services. Undoubtedly, this policy significantly affects implications for airspace sovereignty and limits the authority of the Government in the implementation of the ASEAN Open Sky Agreement.